Movimientos sociales y acción colectiva en Nicaragua : entre la identidad, autonomía y subordinación - Mario Sánchez González; Douglas Castro Quezada; Rony Rodríguez Ramírez; Jorge Guerra Vanegas (Amnis)
This article analyzes the evolution of three social movements (Natives, women and workers) at key moments of the history of Nicaragua: the dictatorship of Somoza (1934-1979), the Sandinista revolution (1979-1990) and the neoliberal era (1990-2000).